Educational equity amidst COVID-19: Exploring the online learning challenges of Bedouin and Jewish Female Preservice Teachers in Israel - Frei-Landau, Rivi; Avidov-Ungar, Orit (Teaching and teacher education, 2022)
Amidst COVID-19, teacher education has shifted to online learning. Although much is known about digital inequity in routine times, little is known about it under constrained conditions, particularly among women of minority groups. The study's goal was to explore the online-learning challenges encountered by (minority) Bedouin female preservice teachers (n = 41) compared to those encountered by (majority) Jewish counterparts (n = 60). Data from reflections (N = 101), focus groups (2), and (68) interviews underwent qualitative-constructivist content analysis. Group comparisons revealed socioculturally-based differential learning pathways, leading to educational inequities. We discuss possible ways to ensure equitable online teacher education using the “digital divide” perspective.